Gestão educacional e assistência estudantil: uma análise das práticas de gestão da assistência estudantil no Instituto Federal da Paraíba Campus João Pessoa - Almeida, Eliene Estevão de (2017)
The social policy of student assistance, with the characteristic of social protection, aims to confront the socioeconomic and cultural vulnerabilities existing in the school context that compromise the presupposition of social inclusion as a horizon of excellence education. From this perspective, the current research aims to analyze the perception of students, technicians and managers of the practices of program management (food, transportation and housing) of student assistance at the Federal Institute of Paraíba Campus João Pessoa. From this perspective, the focus of this investigation is the three permanence programs, that is; Program of food, transportation and housing operationalized with income cutbacks. Regarding the theoretical basis, the theme in question points to the deepening of three analytical categories: public policies (official and in use); Management in the field of education, bureaucratic management and managerial or democratic management, and finally, questions related to student assistance in the conception of social law and the functionalist and / or welfare perspective. Regarding the methodological procedures to achieve the objectives of this qualitative study of the ongoing research, as strategies for data collection we decided to use the interview with the managers and the formation of focus groups with the students and with the professionals inserted in the context of the practice with the intention of ascertaining the perception of these subjects on the management of the AE in the context of the IFPB, notably in the João Pessoa Campus. The methodology should also consist of bibliographical research, monographs, dissertations, theses, articles, editorials and journals. The results point to the predominance of the conception of student assistance as a right, despite the contradictions. With regard to the management of the EA, processes of resistance to changes, the need to expand the professional staff and the establishment of a strategic plan were identified. All of this has compromised the achievement of the purposes of the National Program of Student Assistance. Finally, proposals are pointed out with a view to establishing a new culture in the treatment of the PNAES within the Federal Institute of Paraíba.